2021
DOI: 10.3389/fncel.2021.723308
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of β-1,4-Galactosyltransferase V on Microglial Function

Abstract: β-1,4 Galactosyltransferase V (β-1,4-GalT V) belongs to the β-1,4 galactosyltransferase family, which modifies proteins and plays a vital role in biological function. Our previous study revealed that β-1,4-GalT V was expressed in the cortex and hippocampus and participated in the recovery of spatial learning and memory in rats with traumatic brain injury. However, the expression of β-1,4-GalT V in microglia, resident immune cells in the central nervous system, and its impact on microglia in resting and lipopol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 56 publications
0
2
0
1
Order By: Relevance
“…For instance, several studies have demonstrated the potential of B4GALT5 downregulation to ameliorate insulin resistance by promoting adipogenic commitment and reducing M1 macrophage in ltration [32] . Other researchers have stated that B4GALT5 plays a regulatory role in microglial migration, proliferation, and the release of in ammatory factors [33] . Additionally, B4GALT5 has been shown to regulate the proliferation of breast cancer stem-like cells through glycosylation, speci cally via the Wnt/β-catenin signaling pathway [34] .…”
Section: Discussionmentioning
confidence: 99%
“…For instance, several studies have demonstrated the potential of B4GALT5 downregulation to ameliorate insulin resistance by promoting adipogenic commitment and reducing M1 macrophage in ltration [32] . Other researchers have stated that B4GALT5 plays a regulatory role in microglial migration, proliferation, and the release of in ammatory factors [33] . Additionally, B4GALT5 has been shown to regulate the proliferation of breast cancer stem-like cells through glycosylation, speci cally via the Wnt/β-catenin signaling pathway [34] .…”
Section: Discussionmentioning
confidence: 99%
“…This was accompanied by increased expression of β-1,4-GalT-I and -V mRNAs [ 50 ]. More recent studies have shown that the cortex, hippocampus region, and microglia cells express β-1,4-GalT-V and play an important role in “neuro-inflammation” by way of proliferation and hyper-activation [ 51 ].…”
Section: Inflammation and β-14-galt-vmentioning
confidence: 99%
“…The following supporting information can be downloaded at: . References [ 68 , 69 , 70 , 71 , 72 , 73 , 74 , 75 , 76 , 77 , 78 , 79 , 80 , 81 , 82 , 83 , 84 , 85 , 86 , 104 , 105 , 106 , 107 , 108 , 140 , 141 , 142 , 143 , 144 , 145 , 146 , 147 , 148 , 149 , 150 , 151 , 152 , 153 , 154 , 155 , 156 , 157 , 158 , 159 , 160 , 161 , 162 , 163 , 164 , 165 , 166 , 167 , 168 , 169 , 170 , 171 ,…”
unclassified